Ionic conductivity study on electron beam irradiated polyacrylonitrile-polyethylene oxide gel - 马艺准 庞立龙 朱亚滨 王志光 申铁龙 (Chinese physics B, 2011)
Different mass percent polyacrylonitrile （PAN）-polyethylene oxide （PEO） gels were prepared and irradiated by an electron beam （EB） with energy of 1.0 MeV to the dose ranging from 13 kGy to 260 kGy. The gels were analysed by using Fourier transform infrared spectrum, gel fraction and ionic conductivity （IC） measurement. The results show that the gel is crosslinked by EB irradiation, the crosslinking degree rises with the increasing EB irradiation dose （ID） and the mass percents of both PAN and PEO contribute a lot to the crosslinking; in addition, EB irradiation can promote the IC of PAN-PEO gels. There exists an optimum irradiation dose, at which the IC can increase dramatically. The IC changes of the PAN-PEO gels along with ID are divided into three regions： IC rapidly increasing region, IC decreasing region and IC balanced region. The cause of the change can be ascribed to two aspects, gel capturing electron degree and crosslinking degree. By comparing the IC-ID curves of different mass percents of PAN and PEO in gel, we found that PAN plays a more important role for gel IC promotion than PEO, since addition of PAN in gel causes the IC-ID curve sharper, while addition of PEO in gel causes the curve milder.